2023
DOI: 10.1364/ol.494431
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced femtosecond nonlinear optical response in Mn-doped Cs2AgInCl6 nanocrystals

Abstract: Lead-free halide double perovskite nanocrystals (DPNCs) are emerging materials, recently explored as potential candidates in light-emitting, photovoltaic, and other optoelectronic applications. This Letter reveals unusual photophysical phenomena and nonlinear optical (NLO) properties of Mn-doped Cs2AgInCl6 nanocrystals (NCs) via temperature-dependent photoluminescence (PL) and femtosecond Z-scan measurements. The PL emission measurements suggest that self-trapped excitons (STEs) are present, and more than one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…As per the transmission electron microscopy (TEM) analysis shown in Figure 1(a) and (b), both the pristine and Mn-doped nanocrystals are cubic structured and we have observed that, after doping with the Mn, the NCs size has reduced from 14 to 10 nm which helps in achieving higher quantum efficiency in the latter compared with pristine owing to higher quantum confinement of nanocrystals with reduced size. 44 The UV−visible absorption spectrum is shown in Figure 1(c), and the obtained data matches exactly with the previous literature. 43 The schematic diagram for the preparation of thin films is shown in Figure 1(d), and as shown in the figure, the obtained colloidal NCs are dispersed in toluene with continuous stirring on a hot plate until it dissolves completely.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As per the transmission electron microscopy (TEM) analysis shown in Figure 1(a) and (b), both the pristine and Mn-doped nanocrystals are cubic structured and we have observed that, after doping with the Mn, the NCs size has reduced from 14 to 10 nm which helps in achieving higher quantum efficiency in the latter compared with pristine owing to higher quantum confinement of nanocrystals with reduced size. 44 The UV−visible absorption spectrum is shown in Figure 1(c), and the obtained data matches exactly with the previous literature. 43 The schematic diagram for the preparation of thin films is shown in Figure 1(d), and as shown in the figure, the obtained colloidal NCs are dispersed in toluene with continuous stirring on a hot plate until it dissolves completely.…”
Section: ■ Results and Discussionsupporting
confidence: 88%
“…The synthesized pristine and Mn-doped double perovskite NCs (DPNCs) are confirmed by using basic structural and photophysical characterization techniques. As per the transmission electron microscopy (TEM) analysis shown in Figure (a) and (b), both the pristine and Mn-doped nanocrystals are cubic structured and we have observed that, after doping with the Mn, the NCs size has reduced from 14 to 10 nm which helps in achieving higher quantum efficiency in the latter compared with pristine owing to higher quantum confinement of nanocrystals with reduced size . The UV–visible absorption spectrum is shown in Figure (c), and the obtained data matches exactly with the previous literature …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the Z-scan experiments, a standard setup 27–31 was used with the Ti:sapphire laser amplifier (LIBRA) as the light source, emitting at a 800 nm central wavelength, with a 70 fs pulse duration, and a 1 kHz repetition rate. The estimated peak intensity was about 180 GW cm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…NLO deals with the study of the variation of the polarization density with the incident electric field of light. Since the last few decades, the NLO field has been developed in photonics and optoelectronics, including electro-optic sensors, and telecommunications. Along with inorganic materials, organic materials also show good NLO properties due to their highly delocalized π-conjugated electrons. , The organic molecules possess large and fast nonlinear responses with easy processing, providing advantages for optical applications . Due to the nonlinear Kerr effect, the NLO parameter nonlinear refractive index (NLR) n 2 of material changes with varying the value of the input intensity of the incident light. , There are various processes for measuring the third-order polarizabilities, such as four-wave mixing (FWM), the optical Kerman method, and the Z-scan method. Nonlinear coherent light–matter interaction spatial self-phase modulation , is an easy-to-handle but robust standard experiment to precisely evaluate various NLO parameters such as nonlinear refractive index ( n 2 ) and third-order nonlinear optical susceptibility [χ (3) ].…”
Section: Introductionmentioning
confidence: 99%